Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Halwa Bouquet Di Klampis - Adewiyeh, Nufiyatul; Kurriwati, Nirma (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This research aims to analyze: (1) Assess the impact of product quality on consumer choices. (2) Examining the impact of price on purchasing decisions. (3) To find out whether buyers are influenced by price and product quality. Customers over 17 years old who have made a single purchase of Halwa bouquet products constitute the population used in this quantitative study. Information collected through validated and reliable surveys, followed by analysis and hypothesis testing. According to the findings, all hypotheses put forward are valid. According to primary data, consumers ' choice to buy Halwa bouquet products is influenced by two main factors, namely product quality and price. The strategic importance of attracting and retaining customers through competitive pricing and high product quality is highlighted in the study, which in turn influences their purchasing decisions. Companies can gain valuable insights on how to optimize their pricing and marketing strategies to become more competitive and increase their market share in highly competitive industries from the implications of this study.